PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP KEPUTUSAN PEMBELIAN DI BITTERSWEET BY NAJLA - Gita Nur Fitri; Chatarina Yunita (Jurnal Pijar, 2023)
The study aims to analyze the effect of product quality, brand image, and electronic word of mouth (E-WOM) on purchasing decisions at Bittersweet by Najla. The sampling method is purposive sampling, where a sample of 100 respondents is selected based on predetermined criteria. The population that is the object of research is comprised of consumers of Bittersweet by Najla. Data collection through questionnaires distributed to consumers of Bittersweet by Najla. This research method uses quantitative methods, and data analysis is carried out using multiple linear regression methods by applying the Statistical Package for the Social Sciences (SPSS) software version 24. The results of the research tests show that simultaneously and partially, product quality, brand image, and electronic word of mouth (E-WOM) have a positive and significant influence on purchasing decisions at Bittersweet by Najla. These findings indicate that product quality, brand image, and E-WOM have an important role in shaping consumer purchasing decisions at Bittersweet by Najla.